Comparison of single-session aspiration and ethanol sclerotherapy with laparoscopic de-roofing in the management of symptomatic simple renal cysts - Efesoy, Ozan (Turk J Urol, 2015)
OBJECTIVE: The aim of the study was to compare the efficacy and cost-effectiveness of single-session aspiration and ethanol sclerotherapy with laparoscopic de-roofing in the management of symptomatic simple renal cysts. MATERIAL AND METHODS: Between March 2010 and December 2012, patients with simple renal cysts presenting with pressure and pain symptoms were divided into two groups. In Group 1 following local anesthetic administration, single session percutaneous aspiration with 95% ethanol sclerotherapy (n=38) and in Group 2 transperitoneal laparoscopic de-roofing under general anesthesia (n=42) were performed. The data were evaluated retrospectively and demographic characteristics, duration of operation and hospitalization, complication rates, cost effectiveness, radiological and symptomatic success rates at six month- follow-up were compared between the two groups. RESULTS: The mean age and gender of the patients, cyst diamater, side and localization of the cyst and indications for intervention were similar in two groups. The median course of treatment and hospitalization were signifcantly decreased in Group 1 (respectively 33 min versus 59 min and 6 hours versus 24 hours, p<0.001). As complications in Group 1 fever in two patients (5.3%) and in Group 2 bleeding requiring transfusion in one patient (2.4%) were observed (p=0.495). Total cost was calculated as $ 131.7 in Group 1 and $ 729.8 in Group 2. After the sixth month follow-up control radiological success rates were found to be signifcantly higher in Group 2, while symptomatic success rate is similar in both groups (63.2% versus 95.2%, p<0.001; 94.7% versus 97.6%, p=0.498, respectively). CONCLUSION: Single-session percutaneous aspiration with alcohol sclerotherapy and laparoscopic de-roofing are safe and effective methods in the treatment of symptomatic simple renal cysts. While radiological recurrence rate was higher in single session percutaneous aspiration with alcohol sclerotherapy, however similar symptomatic recurrence rates were seen with laparoscopy. Therefore single session percutaneous aspiration combined with alcohol sclerotherapy seems to be an important option in the treatment of simple renal cysts when considering the duration of the operation, hospitalization and total costs of the process.